Mechanisms and quantification: How anthropogenic aerosols weaken the East Asian summer monsoon - Yiwen Lang; Jing Zhang; Jin Zhao; Yuhang Gong; Tian Han; Xiaoqing Deng; Yuqing Liu (npj Climate and Atmospheric Science)
Abstract Anthropogenic aerosols could weaken the East Asian summer monsoon (EASM). This study investigated the regional effects of varying aerosol optical depth (AOD) on the EASM through qualitative and quantitative analyses for three subregions in eastern China. After assessing 38 CMIP6 models, four models (ACCESS-CM2, CanESM5, MIROC6, and MRI-ESM2-0) were selected for detailed analysis. Results showed that the weakening of EASM was predominantly attributed to anthropogenic aerosols. Increased AOD reduced land-sea temperature and pressure differences, weakening the EASM as indicated by the EASMI. Higher aerosol levels decreased surface shortwave radiation, land surface temperature, and evaporation, weakening the land-sea thermal contrast. Enhanced aerosol-induced cooling increased atmospheric stability and downward flow, suppressing upper air water vapor flux and precipitation. These findings underscore the critical role of anthropogenic aerosols in altering regional climate patterns and the importance of emission control to mitigate their effects on the EASM.